Asine III : supplementary studies on the Swedish excavations 1922 - 1930, fasc. 2 : children lost and found : a bioarchaeological study of Middle Helladic children in Asine with a comparison to Lerna - Ingvarsson-Sundström, Anne, 1964- (Stockholm)
151 s.